Die Region Rhein-Main im Europa der Regionen - Wolf, Klaus (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
Globalisation and regionalisation as the factors of development of cities and densely populated areas represent a new challenge for urban geography. The resulting tasks of geography are represented bz city geography oriented into solving economic-development problems, with the problems of regional cooperation pointed out.
Keywords: Europe; Evropa; Germany; Nemčija; regije; regionalna politika; regionalni razvoj; regionalno planiranje